Red star over Malaya resistance and social conflict during and after the Japanese occupation of Malaya, 1941-46 - Cheah, Boon Kheng (Southeast Asian classic reprints, 2012)
'Red Star Over Malaya' describes inter-racial relations between Malays and Chinese during the final stages of the Japanese Occupation and its aftermath. In 1841, none of the three major races - Malays, Chinese, and Indians - regarded themselves as 'Malayans' with a common identity. When the Occupation forcibly cut them off from China, Chinese residents began to look inwards towards Malaya and stake political claim, leading inevitably to a political contest with the Malays. As the country advanced towards nationhood and self-government, there was tension between traditional loyalties to the Malay rulers and the states, or to ancestral homelands elsewhere, and the need to cultivate an enduring loyalty to Malaya on the part of those who would make their home there in future. When Japanese forces withdrew from the countryside, the Chinese guerrillas of the communist-led resistance movement, the Malayan People's Anti-Japanese Army (MPAJA), emerged from the jungle and took control of many smaller towns and villages. When the British Military Administration sought to regain control of these liberated areas, the ensuing conflict set the tone for future political conflicts and marked a crucial stage in the history of Malaya. 'Red Star Over Malaya' draws on extensive archival research to provide a riveting account of the way the Japanese Occupation reshaped colonial Malaya, and of the tension-filled months that followed Japan's surrender. The book is fundamental to an understanding of social and political developments in Malaysia during the second half of the 20th century.